ANALISIS MINAT BELI KONSUMEN PRODUK SEPATU OLAHRAGA NIKE - Raditya Hawari (2020)
The research is a quantitative research that aims to determine the influence of Online Social Media Marketing, Sales Promotion, advertisement on purchase intention product of Nike sneakers. The population in this study was a domed Nike sneakers user in Tangeran Selatan. The sample size was taken 75 respondens, with nonprobability sampling method, especially purposive sampling. Data collection done through questionnaires. Analytical technique used is the method pf analysis PLS (Partial Least Square). The result of this study indicate that (1) Online & Social Media Marketing has a significant influence on purchase intention with coefficient value of 0,001. (2) Sales Promotion has a significant influence on purchase intention with coefficient value of 0,020. (3) advertisement has a significant influence on purchase intention with coefficient value of 0,000